Type V Pouch Colon, Prune Belly Syndrome, and Congenital Anterior Urethrocutaneous Fistula - Prince Raj; Hirendra Birua (EL-Med-Pub, 2017)
Congenital pouch colon (CPC) or short colon syndrome is a rare type of anorectal malformation(ARM). Type V is the rarest form of CPC. We present a 1-day-old male child with type V CPC with prune belly syndrome and congenital anterior urethrocutaneous fistula (CAUF).